Differential expression of the T-cell inhibitor TIGIT in glioblastoma and MS. Issue 3 (May 2020) - Lucca, Liliana E.; Lerner, Benjamin A.; Park, Calvin; DeBartolo, Danielle; Harnett, Brian; Kumar, Varun P.; Ponath, Gerald; Raddassi, Khadir; Huttner, Anita; Hafler, David A.; Pitt, David
Abstract : Objective: To identify coinhibitory immune pathways important in the brain, we hypothesized that comparison of T cells in lesions from patients with MS with tumor-infiltrating T cells (TILs) from patients with glioblastoma multiforme may reveal novel targets for immunotherapy. Methods: We collected fresh surgical resections and matched blood from patients with glioblastoma, blood and unmatched postmortem CNS tissue from patients with MS, and blood from healthy donors. The expression of TIGIT, CD226, and their shared ligand CD155 as well as PD-1 and PDL1 was assessed by both immunohistochemistry and flow cytometry. Results: We found that TIGIT was highly expressed on glioblastoma-infiltrating T cells, but was near-absent from MS lesions. Conversely, lymphocytic expression of PD-1/PD-L1 was comparable between the 2 diseases. Moreover, TIGIT was significantly upregulated in circulating lymphocytes of patients with glioblastoma compared with healthy controls, suggesting recirculation of TILs. Expression of CD226 was also increased in glioblastoma, but this costimulatory receptor was expressed alongside TIGIT in the majority of tumor-infiltrating T cells, suggesting functional counteraction. Conclusions: The opposite patterns of TIGIT expression in the CNS between MS and glioblastoma reflects the divergent features of the immune response in these 2 CNS diseases. These data raise the possibility that anti-TIGIT therapy may be beneficial for patients with glioblastoma.